Risk of rupture of small anterior communicating artery aneurysms is similar to posterior circulation aneurysms. - Bijlenga, P; Ebeling, C; Jaegersberg, M; Summers, P; Rogers, A; Waterworth, A; Iavindrasana, J; Macho, J; Pereira, V; Bukovics, P; Vivas, E; Sturkenboom, M; et al. (2013)
BACKGROUND AND PURPOSE: According to the International Study of Unruptured Intracranial Aneurysms (ISUIA), anterior circulation (AC) aneurysms of <7 mm in diameter have a minimal risk of rupture. It is general experience, however, that anterior communicating artery (AcoA) aneurysms are frequent and mostly rupture at <7 mm. The aim of the study was to assess whether AcoA aneurysms behave differently from other AC aneurysms. METHODS: Information about 932 patients newly diagnosed with intracranial aneurysms between November 1, 2006, and March 31, 2012, including aneurysm status at diagnosis, its location, size, and risk factors, was collected during the multicenter @neurIST project. For each location or location and size subgroup, the odds ratio (OR) of aneurysms being ruptured at diagnosis was calculated. RESULTS: The OR for aneurysms to be discovered ruptured was significantly higher for AcoA (OR, 3.5 [95% confidence interval, 2.6-4.5]) and posterior circulation (OR, 2.6 [95% confidence interval, 2.1-3.3]) than for AC excluding AcoA (OR, 0.5 [95% confidence interval, 0.4-0.6]). Although a threshold of 7 mm has been suggested by ISUIA as a threshold for aggressive treatment, AcoA aneurysms <7 mm were more frequently found ruptured (OR, 2.0 [95% confidence interval, 1.3-3.0]) than AC aneurysms of 7 to 12 mm diameter as defined in ISUIA. CONCLUSIONS: We found that AC aneurysms are not a homogenous group. Aneurysms between 4 and 7 mm located in AcoA or distal anterior cerebral artery present similar rupture odds to posterior circulation aneurysms. Intervention should be recommended for this high-risk lesion group.